Comparative estimation of meningiomas and neuroepithelial brain tumors surgical treatment results using standard methods and modern technologies in early postoperative period - Yekimov, A. A.; Sakovich, V. P.; Kotlyarov, E. V.; Shalyapin, V. G. (Ukrainian Neurosurgical Journal, 2008)
The results of surgical treatment of patients with cerebral glioma and meningioma of different localization were analyzed. The object of the clinical study were 70 patients, operated at in the same conditions and by the same neurosurgeons, 34 of them — using new technologies. All the patients had clinical symptoms of the disease. The examination included CT, MRI MR-angiography and preoperative angiography. One of the main tendencies for modern neurosurgery development is the navigation and electrophysiology technologies application for the purpose of surgical trauma minimizing. New technologies application in mass cerebral lesions surgical treatment provides the invasiveness considerable diminish and surgical intervention duration and intraoperative hemorrhage significant decrease.